Classifications of users on online platforms using machine learning techniques - Михайлов, Н. О. (Київський національний університет імені Тараса Шевченка, 2022)
Online platforms have become an integral part of our lives, and the number of users is increasing by the day. From social media platforms to e-commerce websites, these platforms are used by millions of people around the world. With such a large user base, it is essential for these platforms to classify their users based on their behavior, preferences, and interests. This paper explores how machine learning can be used to classify users on online platforms. When classifying users, they are divided into different categories based on their characteristics. By analyzing user behavior and preferences, online platforms can personalize their services and provide a better user experience. Machine learning techniques can help online platforms automate the classification process and reduce human effort. In this article, the behavioral classification of users on online platforms will be discussed in detail. Pages of the article in the issue: 66 - 71 Language of the article: Ukrainian

Онлайн-платформи стали невід’ємною частиною нашого життя, а кількість інтернет користувачів зростає з кожним днем. Від платформ соціальних медіа до веб-сайтів електронної комерції, цими платформами користуються мільйони людей у всьому світі. З такою великою базою юзерів цим платформам важливо класифікувати своїх користувачів на основі їх поведінки, уподобань та інтересів. У цій статті досліджується, як машинне навчання можна використовувати для класифікації користувачів на онлайн-платформах. Класифікуючи користувачів, їх поділяють на різні категорії на основі їхніх характеристик. Аналізуючи поведінку та вподобання користувачів, онлайн-платформи можуть персоналізувати свої послуги та забезпечувати кращий досвід користувачів. Методи машинного навчання можуть допомогти онлайн-платформам автоматизувати процес класифікації та зменшити людські зусилля. У цій статі буде детально розглянута поведінкова класифікація користувачів на онлайн-платформах.
Класифікація користувачів на онлайн платформах методами машинного навчання
Keywords: user classification; user analysis; сluster analysis; association rules; neural networks; класифікація користувачів; аналіз користувачів; кластеризація; правила асоціацій; нейронні мережі